Review of A global security system: an alternative to war. - Mische, Patricia M. (In Factis Pax: Journal of Peace Education and Social Justice, 2017)
Book Review A global security system: an alternative to war. 2016 edition. Main authors: Kent Shifferd, Patrick Hiller, David Swanson, with input from many others. World Beyond War, 2016, 88 pp., US 16.97 (paperback), free digital download, ISBN 978-0-9980859-1-3